The Role and Mechanism of Histone Deacetylases in Acute Kidney Injury - Zhou, Xun; Chen, Hui; Shi, Yingfeng; Ma, Xiaoyan; Zhuang, Shougang; Liu, Na (Frontiers in Pharmacology, 2021)
Abstract: Acute kidney injury (AKI) is a common clinical complication with an incidence of up to 8%-18% in hospitalized patients. AKI is also a complication of COVID-19 patients and is associated with an increased risk of death. In recent years, numerous studies have suggested that epigenetic regulation is critically involved in the pathophysiological process and prognosis of AKI. Histone acetylation, one of epigenetic regulations is negatively regulated by histone deacetylases (HDACs). Increasing evidence indicates that HDACs play an important role in the pathophysiological development of AKI by regulation of apoptosis, inflammation, oxidative stress, fibrosis, cell survival, autophagy, ATP production and mitochondrial biogenesis(MB). In this review, we summarize and discuss the role and mechanism of HDACs in the pathogenesis of AKI.